Consequences of the combined loss of BOK and BAK or BOK and BAX - Ke, F (Nature Publishing Group, 2013)
The multi-BCL-2 homology domain pro-apoptotic BCL-2 family members BAK and BAX have critical roles in apoptosis. They are essential for mitochondrial outer-membrane permeabilization, leading to the release of apoptogenic factors such as cytochrome-c, which promote activation of the caspase cascade and cellular demolition. The BOK protein has extensive amino-acid sequence similarity to BAK and BAX and is expressed in diverse cell types, particularly those of the female reproductive tissues. The BOK-deficient mice have no readily discernible abnormalities, and its function therefore remains unresolved. We hypothesized that BOK may exert functions that overlap with those of BAK and/or BAX and examined this by generating Bok(−/−)Bak(−/−) and Bok(−/−)Bax(−/−) mice. Combined loss of BOK and BAK did not elicit any noticeable defects, although it remains possible that BOK and BAK have critical roles in developmental cell death that overlap with those of BAX. In most tissues examined, loss of BOK did not exacerbate the abnormalities caused by loss of BAX, such as defects in spermatogenesis or the increase in neuronal populations in the brain and retina. Notably, however, old Bok(−/−)Bax(−/−) females had abnormally increased numbers of oocytes from different stages of development, indicating that BOK may have a pro-apoptotic function overlapping with that of BAX in age-related follicular atresia.